PERCEPTION OF INTELLECTUAL STIMULATION, CREATIVITY AND INNOVATION AMONG HEALTH MANAGERS WORKING IN TERTIARY LEVEL HOSPITALS - Shahzad, Saadia; Zareen, Humaira (Journal of Ayub Medical College Abbottabad, 2011)
Background: Management in health sector is becoming focus of attention world over being an important subject due to resource crunch particularly in developing countries. Beside sociodemographic factors, poor management in health sector is also an important factor responsible for poor health in developing countries. Moreover, there is gross lack of effective leadership in our national setup. It is necessary for health managers to be well versed with the knowledge about emerging theories, concepts and new philosophies of management/administration and leadership. This anthropological study was done to assess the perception and knowledge of Intellectual stimulation, creativity and innovation among the health managers working in the tertiary level hospitals of Lahore. Methods: This qualitative study was conducted in two public sector tertiary care hospitals of Lahore. Observation and in-depth interviews were conducted for data collection. Open ended questionnaire, developed on the lines of Multifactor Leadership Questionnaire was used. One main domain of Intellectual stimulation and its variables were developed and emergence of different themes was noted. Results: In the domain of Intellectual stimulation all the participants of the study showed positive themes for the variable of creativity. Seven of the health managers showed positive themes for the variable of innovation, where as three health managers showed negative responses. Conclusion: Health managers with management/administration qualification had better concept about the key ideas of Intellectual stimulation, creativity and innovation; as compared to those who were working at these managerial posts on the basis of their long term experience only. Female health managers were stronger in building their team members on a broader horizon as a wholesome personality and not just taking the daily routine work. Keywords: Intellectual stimulation, creativity, innovation, health managers